2017
DOI: 10.11138/ccmbm/2017.14.1.227
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia and osteomalacia after bariatric surgery

Abstract: SummaryIntroduction. Obesity has become a major health problem not only in industrialized societies but also in developing countries. Multiple studies have shown that bariatric surgery has been effective in reducing substantial amount of weight and also the comorbidities and is being performed more frequently as an established treatment. Due to anatomical and physiological alterations after surgery that impairs absorption of vitamin D and calcium, two fundamental factors in bone formation, their intestinal abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Obesity is the critical risk factor for metabolic diseases including type 2 diabetes, cardiovascular disease, metabolic syndrome (encompassing hypertension, dyslipidemia, and insulin resistance), and non-alcoholic fatty liver disease. , The etiology of obesity involves complicated interactions between genetic and environmental factors such as dietary nutrients and physical activity . In addition, numerous investigations have indicated that gut dysbiosis is intricately involved in the development of obesity , and obesity-related metabolic diseases. , …”
Section: Introductionmentioning
confidence: 99%
“…Obesity is the critical risk factor for metabolic diseases including type 2 diabetes, cardiovascular disease, metabolic syndrome (encompassing hypertension, dyslipidemia, and insulin resistance), and non-alcoholic fatty liver disease. , The etiology of obesity involves complicated interactions between genetic and environmental factors such as dietary nutrients and physical activity . In addition, numerous investigations have indicated that gut dysbiosis is intricately involved in the development of obesity , and obesity-related metabolic diseases. , …”
Section: Introductionmentioning
confidence: 99%
“…The extensive anatomic changes to the gastrointestinal tract caused by bariatric surgery are known to cause various macronutrient deficiencies, including protein-calorie malnutrition and fat malabsorption, which can, in turn, lead to hypocalcemia and osteomalacia. 22,23…”
Section: Discussionmentioning
confidence: 99%
“…The extensive anatomic changes to the gastrointestinal tract caused by bariatric surgery are known to cause various macronutrient deficiencies, including protein-calorie malnutrition and fat malabsorption, which can, in turn, lead to hypocalcemia and osteomalacia. 22,23 There is no current consensus on the effects of bariatric surgery fracture risk. A 2012 retrospective cohort study in the United Kingdom (n = 10,442) and a 2020 retrospective cohort study in the United States (n = 49,113) found that bariatric surgery had no effect on the risk of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Значимость контроля за состоянием костного метаболизма после бариатрической хирургии подтверждается множеством описанных случаев низкотравматичных переломов костей позвоночника и проксимального отдела бедра через несколько лет после проведения данных операций [35,36,37].…”
unclassified